(untitled) (Biological Sciences - PJSIR, 2008)
. Some quinazolone derivatives of 2-methyl-3-(arylthiocarbamido) quinazol-4-ones (2) and 2-methyl-3- (arylidencarboxamido) quinazol-4-ones (3) have been synthesized and assayed for their possible antibacterial activity against Bacillus subtilis, Bacillus cereus, Salmonella aureus, Salmonella lutae and antiviral activity against Gomphrena mosaic virus. Some of these compounds show notable activity.